Development of water resources protection planning and environmental design in urban water conservancy landscape based on ecological concept - Hua Huang (Water Supply, 2023)
With the development of society, water resources are gradually scarce and water pollution is becoming increasingly serious, which would seriously restrict the development of the urban economy. In response to the current problems of water scarcity and severe water pollution, this article will study the key points of urban environmental design development based on ecological concepts. This article will also use ecological concepts to divide water function zones based on different pollution-carrying capacities in different regions, which can be mainly divided into two levels. In the experimental analysis section, the Xiongan New Area will be analyzed. This article randomly selected three regions in the Xiongan New Area and studied the utilization rate of various types of water in these regions. The pollution capacity and main water resources of each region in the functional area were planned and designed. Through experiments, it can be found that based on ecological concepts, it is beneficial to improve the pollutant-carrying capacity of each functional area and reduce the total amount of ammonia nitrogen. HIGHLIGHT The average utilization rates of these three types of water in 10 administrative regions were 93.01, 93.3, and 93.11%, respectively. Based on ecological concepts, it can help better water resources planning and improve the city's pollution capacity.;